PENINGKATAN MUTU DAN KUALITAS LAHAN PERTANIAN MASYARAKAT MELALUI REKAYASA KESUBURAN TANAH DAN SISTEM IRIGASI SPRINGKLER - Tresjia Corina Rakian; Hamirul Hadini; Zulfikar Zulfikar; Resman Resman; Agustono Slamet; La Ode Rustam (Jurnal Pengabdian NUSANTARA, 2022)
Mokoau Village, Kambu District, Kendari City, Southeast Sulawesi, with partners/target audiences of the Nanga-Nanga Makmur Farmer Group. The Nanga-nanga Makmur Farmer Group is a farmer group that has been established by the Kendari City Agriculture Office in 2020. The problems encountered in the farmer group include land quality in this case low soil fertility, knowledge of fertilization techniques and also minimal organic fertilizer production. In addition, agricultural waste and secondary vegetation which are widely available but have not been optimally utilized as raw materials for engineering soil fertility and nutrient sources for cultivated plants and also irrigation systems/plant watering methods, especially those who carry out manual vegetable cultivation businesses. The solutions and targets offered are conducting technical guidance and demonstration of vegetable crop cultivation plots and the manufacture of secondary vegetation-based fertilizers for soil fertility engineering, as well as transferring sprinkler irrigation system technology. The results obtained from the solutions provided are (1) improving the quality of agricultural land, especially soil fertility through the use of organic fertilizers based on secondary vegetation and irrigation systems using sprinklers, (2) increasing the knowledge and skills of farmer group members about the manufacture of fertilizer products for soil fertility engineering. and some group members also make their own at their respective homes. The results made independently were judged to have succeeded and met the requirements as organic fertilizer, (3) increased knowledge of farmer group members in improving the quality and quality of agricultural land through modification of integrated farming techniques and sprinkler model irrigation systems. Sprinkler irrigation technology has never been carried out by partner groups, so through this activity it has added new insights and new skills to increase their land productivity and also streamline water use and time and there are technological innovations carried out jointly between partner farmer group members, students KKN and supervisors are real efforts in transferring knowledge in an effort to apply agricultural technology to partner groups